2009
DOI: 10.1111/j.1464-5491.2008.02610.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodialysis is associated with changes in cutaneous microcirculation in diabetes mellitus

Abstract: Aims To examine the cutaneous microcirculation on the dorsum of the foot before, during and after haemodialysis in diabetic and non-diabetic patients. MethodsFourteen age-matched patients (seven diabetic, seven non-diabetic) without active foot ulceration were studied. Cutaneous microcirculation was assessed using a micro-lightguide spectrophotometer to measure venous oxygen saturation and relative blood flow determined at two tissue depths: 2 and 6 mm. Cumulative relative changes of each parameter during haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 17 publications
(34 reference statements)
1
23
1
2
Order By: Relevance
“…The percentage of diabetics was consistent with the Dutch average. In the national NECOSAD cohort diabetic nephropathy was the primary kidney disease only in 16% [26]. We included no patients with vasculitis; atherosclerosis was not objectified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of diabetics was consistent with the Dutch average. In the national NECOSAD cohort diabetic nephropathy was the primary kidney disease only in 16% [26]. We included no patients with vasculitis; atherosclerosis was not objectified.…”
Section: Resultsmentioning
confidence: 99%
“…Tissue PO 2 and tissue oxygen saturation was consistently found to decrease throughout HD [26,27,28]. However, laser doppler flux was found to increase after HD in one study [29].…”
Section: Discussionmentioning
confidence: 99%
“…Dialysis-specific factors that have been implicated in the development of PAD include vintage and malnutrition [25,33]. Furthermore, two studies have reported an intradialytic drop in microvascular blood flow or tissue oxygenation (transcutaneous oxygen tension) during hemodialysis sessions [35,36], which is most marked among subjects with diabetes [36]. It is thought that huge fluid shifts (and the resultant hemodynamic changes) during dialysis are responsible for this dialysis-mediated tissue hypoperfusion and that this may worsen any underlying PAD and also lead to friable skin and impaired wound healing.…”
Section: Pad In Advanced Ckd and Esrdmentioning
confidence: 99%
“…One possible explanation is that dialysis induces changes in the circulation of the foot, which differ between patients with and without diabetes. A recent small study looking at tissue oxygenation as measured by TcpO 2 (transcutaneous oxygen pressure) in patients with diabetes showed a trend towards a fall in TcpO 2 during and after haemodialysis [16], and a further small study examining the cutaneous microcirculation of the foot before, during and after haemodialysis using a micro-lightguide showed an increase in blood flow in non-diabetics, whereas in diabetic patients the flow fell [17]. …”
Section: Causes Of Foot Ulcers In Patients With Diabetes and Ckdmentioning
confidence: 99%